Philosophical Perspective on Health: A Review Paper - Krishna Bahadur G. C.; Ejan Rajbhandari (Prāgyik Prabāha, 2024)
Theory and philosophy guide an individual along a distinct path. Furthermore, because human health includes a number of different characteristics, a single theory is not adequate to properly grasp human health on its own. Therefore, the purpose of this study is to explore philosophical views on health. This overview discusses only the biomedical, functionalist, post-structuralist (as defined by Foucault), and Marxist viewpoints on health. Every single philosopher has their own unique lines of reasoning and reasons that support their beliefs. For a more comprehensive investigation, which should also include investigation of other possibilities, we suggest doing an additional systematic review.